The Role of Forensic Accounting in Detecting Financial Frauds - Nursansiwi, Dwi Arini (Accounting Studies and Tax Journal (COUNT), 2024)
This research targets to explore the important role of forensic accounting in detecting and preventing financial fraud amidst dynamic changes within the business world. Through a systematic literature review method, we explore the contribution of forensic accounting through in-depth investigations of financial records, identification of suspicious activity patterns, collaboration with security and legal authorities, and fraud prevention through financial control design. The results verify that forensic accounting isn't the most effective retrospective tool, but also proactive in mitigating the chance of financial fraud in the future. This has a look at summarizing these findings with the reason of presenting a holistic view of the essential role of forensic accounting in keeping a company's financial integrity.